2010
DOI: 10.1007/s10773-010-0537-5
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in Supersymmetric Theory in Restricted Chromodynamics

Abstract: The study of superconductivity, dual superconductivity and color superconductivity has been undertaken through the breaking of super symmetric gauge theory in restricted chromo dynamics (RCD) which automatically incorporates the condensation of monopoles and dyons leading to confining and superconducting phases. Dyonic supermultiplets in N = 1 super symmetry have been obtained quantum mechanically in RCD and it has been shown that dyon appears in RCD theory only through restricted part of the generalized poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The unrestricted part B * μ of the gauge potential describes the monopole flux of color isocharges. The unrestricted part B * μ is the dual potential associated with charged gluons W ± μ and leads to condensation of monopoles and the resultant state of chromo magnetic superconductivity as shown in our earlier papers [27][28][29][30][31][32].…”
Section: Embedded Monopoles In Restricted Chromodynamics In Su(2) Gaumentioning
confidence: 99%
See 1 more Smart Citation
“…The unrestricted part B * μ of the gauge potential describes the monopole flux of color isocharges. The unrestricted part B * μ is the dual potential associated with charged gluons W ± μ and leads to condensation of monopoles and the resultant state of chromo magnetic superconductivity as shown in our earlier papers [27][28][29][30][31][32].…”
Section: Embedded Monopoles In Restricted Chromodynamics In Su(2) Gaumentioning
confidence: 99%
“…Perhaps the most important aspect of monopoles and dyons in physics is their role in the mechanism of quark confinement [16][17][18][19][20][21] along the lines of dual Meissner effects [22][23][24][25][26] leading to dual superconductivity as discussed in our recent papers [27][28][29][30][31][32] by employing dual gauge potential where magnetic degree of freedom manifestly appears in the partition function.…”
mentioning
confidence: 99%
“…In the process of current understanding of superconductivity, in a series of papers [1][2][3][4][5][6][7][8][9] we have conceived its hopeful analogy with QCD and demonstrated that the essential features of superconductivity i.e., the Meissner effect and flux quantization, provide the vivid models for actual confinement mechanism in QCD. The condensation of magnetic monopole incorporates the state of magnetic superconductivity and the notion of chromo magnetic superconductor [10] where the Meissner effect confining magnetic field in ordinary superconductivity would be replaced by the chromo-electric Meissner effect (the dual Meissner effect),which would confine the color electric flux.…”
Section: Introductionmentioning
confidence: 99%
“…The study of vacuum structure of N = 2 supersymmetric QCD, based on the gauge group SU (2) with N f = 2 flavors of massive hypermultiplet quark, has recently been undertaken [17] in the presence of non-zero baryon chemical potential and it has been found, by numerical analysis, that the baryon number is broken as a consequence of SU(2) strong gauge dynamics so that the color superconductivity dynamically takes place at the non-SUSY vacuum. We have recently undertaken the studies of superconductivity, dual superconductivity and color superconductivity in restricted chromodynamics [18][19][20] and supersymmetric gauge theories [21,22] with quark multiplets and quark chemical potential at classical and quantum levels.…”
Section: Introductionmentioning
confidence: 99%